Endophytic fungi as a promising source of antiviral active compounds: A Review - Septiana, Eris (Jurnal Biologi Udayana; Vol 24 No 1 (2020): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2020.v24.i01.p04, 2020)
Viral infections are still a problem in all countries. Vaccination and antiviral drugs are still being done as an effort to tackle viral infections. The emergence of new virus serotypes that are resistant to existing antiviral drugs has increased the search for new natural antiviral compounds. Endophytic fungi are one of the potential sources of antiviral which is abundant in nature. Several antiviral compounds that are active against several types of viruses that cause infections in humans have been isolated from endophytic fungi. Emodin from endophytic fungi Aspergillus versicolor, aspergillipeptides D from Aspergillus sp., and altertoxin V from Alternaria tenuissima have in vitro antiviral activity against the Hepatitis C, Herpes Simplex, and Human Immunodeficiency viruses respectively. While the catechin from Annulohypoxylon ilanense, norquinadoline A from Cladosporium sp., and isochaetochromin D1 from Fusarium sp. have in silico SARS-CoV-2 inhibitory activity. The development of antiviral active compounds from endophytic fungi needs to be improved. The development includes the optimal method of isolating active compounds, the mechanism of action, in vivo assay to pre-clinical and clinical trials. Optimal development of antiviral compounds from endophytic fungi is expected to produce new antiviral drugs that are more effective in the treatment of viral infections.